KAJIAN JALUR EVAKUASI BENCANA DI GEDUNG BELAJAR PONDOK PESANTREN AL MUKMIN KABUPATEN SUKOHARJO - suyanto yanto yanto; Muhammad Zainuddin (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
ABSTRACT Indonesia is an earthquake-prone area so that several large earthquakes cause a lot of damage. The city of Surakarta has experienced an earthquake that caused severe damage and currently based on the results of the mapping conducted by the Ministry of Energy and Mineral Resources, the city of Surakarta is included in the red zone area or the danger area of ​​a tectonic earthquake. Given that the Al Mukmin Islamic Boarding School is located on the border of the city of Surakarta, which has high-rise school buildings and dormitories that are also multi-storey with the number of students living in dormitories approaching 1,400 people, it is necessary to immediately arrange disaster risk management by mitigating and preparing for earthquake disasters. The goal is the preparation of an evacuation route map in the Al Mukmin Sukoharjo Islamic Boarding School learning building. In order to achieve the goals that have been set, the method used is observation of evacuation routes and plans for installing safety signs. The results of the service in the form of the arrangement of evacuation routes for the boys' and girls' learning buildings as well as plans for the installation of safety signs and the location of the gathering point have been prepared. The conclusion is that field observations in order to recognize the existence of disaster risk must be carried out so that the construction of evacuation routes and places for installing safety signs can be arranged and carried out properly Keywords: Disaster Evacuation Route, Learning Building, Islamic Boarding School